Influence of Life Style and Attitude Toward Trust and Repeat Purchase Intentions on Social Media Users (Study On Instagram Users in Malang) - Intan Nurlaily; Noermijati Noermijati; Ananda Sabil Hussein (Sekolah Pascasarjana Universitas Brawijaya, 2017)
This research is discussed about Lifestyle and trust influenced by Repurchase intention trough attitude. The aims of this research is to understand Influence of life style on the intention repurchasing consumers, Effect of trust on the intention repurchasing consumers, Influence of attitudes toward the purchase intention of re-consumers, Influence of life style to the attitude of repeat purchases of consumer, Effect of trust on the attitudes of repeat purchase consumer, the effect of life style of the consumer repeat purchase intention mediated by the attitude of the people of Malang City, the influence of trust on consumer repeat purchase intention mediated by attitude. Data analysis using Partial Least Square (PLS) analysis methods toward Malang Citizen. This result research has shown that Life style variable has a positive and significant effect on the Buying Intention, trust has a positive and significant impact on the Buying Intention, attitude variable has a positive and significant impact on the Buying Intention, lifestyle have positive and significant effect to consumer attitude, trust has a positive and significant impact on consumer attitudes, attitude is indirectly able to influence the relationship between Life style and Intention Purchase, attitude is indirectly able to influence the relationship between Trust and Intention Purchase.